2023
DOI: 10.1002/bco2.237
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lifestyle changes (diet, exercise and stress reduction) on prostate cancer tumour biology and patient outcomes: A systematic review

Abstract: Background The mostly indolent natural history of prostate cancer (PCa) provides an opportunity for men to explore the benefits of lifestyle interventions. Current evidence suggests appropriate changes in lifestyle including diet, physical activity (PA) and stress reduction with or without dietary supplements may improve both disease outcomes and patient's mental health. Objective This article aims to review the current evidence on the benefits of all lifestyle programmes for PCa patients including those aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…Specifically, observational studies have consistently shown that vigorous exercise after cancer diagnosis leads to more favorable oncological outcomes [29,[38][39][40]. While a recent systematic review conducted by Dovey et al revealed a positive influence of PA on mental health for PCa patients, with 10 out of 15 articles supporting this connection; additionally, concerning oncological outcomes, 26 out of 44 studies demonstrated a positive impact, especially for moderate to vigorous PA, further emphasizing the potential benefits of exercise in the context of PCa [41]. Consequently, it has been incorporated into the ASCO Clinical Practice Guidelines for Prostate Cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, observational studies have consistently shown that vigorous exercise after cancer diagnosis leads to more favorable oncological outcomes [29,[38][39][40]. While a recent systematic review conducted by Dovey et al revealed a positive influence of PA on mental health for PCa patients, with 10 out of 15 articles supporting this connection; additionally, concerning oncological outcomes, 26 out of 44 studies demonstrated a positive impact, especially for moderate to vigorous PA, further emphasizing the potential benefits of exercise in the context of PCa [41]. Consequently, it has been incorporated into the ASCO Clinical Practice Guidelines for Prostate Cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to advanced drugs and precise surgery, some common life factors also perform great in uence on the outcomes of patients, such as alcohol consumption, smoking status and BMI [5][6][7]. Although studies have demonstrated the appropriate lifestyle could provide bene ts for the prognosis of individuals with prostate cancer, it's still di cult to make perfect personal life recommendations for patients due to the heterogeneity of this disease and the inconsistent research results [8,9], so we conducted this study to investigate the effects of alcohol consumption, smoking status and BMI on prostate cancer.…”
Section: Introductionmentioning
confidence: 99%